Whisper network [large type] - Baker, Chandler (Thorndike Press large print basic series, 2019)
Sloane, Ardie, Grace, and Rosalita have worked at Truviv, Inc. for years. The sudden death of Truviv's CEO means their boss, Ames, will take over the company. Ames has always been surrounded by whispers about how he treats women. Those whispers have been ignored by those in charge. This time, when they find out Ames is making an inappropriate move on a colleague, they've decided enough is enough. Sloane and her colleagues' decision to take a stand sets in motion a catastrophic shift in the office. Lies will be uncovered. Secrets will be exposed. Their lives -- as women, colleagues, mothers, wives, friends, even adversaries -- will change dramatically as a result.